The Relationship Between Education, Occupation, and Nutritional Status with Fasting Blood Glucose Levels in Type II Diabetes Mellitus Patients at Jasa Kartini Hospital Tasikmalaya City in 2023 - Nurgajayanti, Cendi; Susilawati, Tri Nugraha; Wiboworini, Budiyanti (Nusantara Science and Technology Proceedings, 2024)
The World Health Organization states that diabetes mellitus is caused by several contributing factors including age, gender, education, lifestyle, physical activity, obesity, and family history. This study aims to investigate the relationship between education, occupation, and nutritional status, with fasting blood glucose levels in type 2 diabetes mellitus patients at the outpatient department of Jasa Kartini Hospital in Tasikmalaya City in 2023. An analytical observational study with a cross-sectional design was conducted using secondary data from medical records of 210 samples of diabetes mellitus patients from January to December 2023. Simultaneous assessments were made for each variable, namely education, occupation, nutritional status, and fasting blood glucose levels. The analysis results indicate that the relationship between education and fasting blood glucose levels yielded a p-value of 0.032, while the relationship between occupation and fasting blood glucose levels yielded a p-value of 0.029. However, the relationship between nutritional status and fasting blood glucose levels resulted in a p-value of 0.450. There is a relationship between education and fasting blood glucose levels, there is a relationship between occupation and fasting blood glucose levels, and there is no relationship between nutritional status and fasting blood glucose levels.